2008
DOI: 10.1211/jpp.60.6.0016
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity of the chloroform extract of the roots from Arctium lappa L.

Abstract: Arctium lappa L. is used in folk medicine as a diuretic, depurative and digestive stimulant and in dermatological conditions. The objective of this study was to evaluate the effect and the possible mechanisms involved in the gastroprotective effects of a chloroform extract (CE) of the roots from A. lappa and its fractions. Oral pretreatment with CE (10, 30 and 100 mg kg(-1)) significantly reduced gastric lesions induced by ethanol by 61%, 70% and 76%, respectively. Oral administration of CE (100 mg kg(-1) per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Burdock (Arctium lappa L.), a biennial plant belonging to the Compositae family, has been cultivated in Eastern Asian countries, particularly in Taiwan, China and Japan for use in cooking and in folk medicine as a diuretic, antipyretic and blood purifying agent (8-10). Pharmacologically, burdock has been identified to possess hepatoprotective (11,12), desmutagenic (13), antibacterial (14,15), gastroprotective (16,17), anti-hypoglycemic (18,19), anti-hypolipidemic (20), anti-inflammatory (21), antifatigue (22), antioxidant (10,21,23), body weight management (24) and aphrodisiac (25) activities. Therefore, burdock-containing health drinks and foods are widely consumed in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Burdock (Arctium lappa L.), a biennial plant belonging to the Compositae family, has been cultivated in Eastern Asian countries, particularly in Taiwan, China and Japan for use in cooking and in folk medicine as a diuretic, antipyretic and blood purifying agent (8-10). Pharmacologically, burdock has been identified to possess hepatoprotective (11,12), desmutagenic (13), antibacterial (14,15), gastroprotective (16,17), anti-hypoglycemic (18,19), anti-hypolipidemic (20), anti-inflammatory (21), antifatigue (22), antioxidant (10,21,23), body weight management (24) and aphrodisiac (25) activities. Therefore, burdock-containing health drinks and foods are widely consumed in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…– is still valued as a plant with antirheumatic, diuretic and diaphoretic effects [17, 19]. Recent studies document a gastroprotective activity [24] and hepatoprotective effects [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Coconut ( Cocos nucifera ) showed antiulcerogenic activity [413], as did Yarrow ( Achillea millefolium ) [414, 415], as well as Arctium lappa [416418]. Schütz et al [419], H.-G. Grigoleit and P. Grigoleit [420], and You et al [421] reported that Taraxacum officinale (Dandelion) relieved oxidative stress and has gastroprotective effects and Capsella bursa-pastoris is well known for its antiinflammatory and hepatoprotective function [422–424].…”
Section: Two Decades Of Traditional Medicine Research In Northern mentioning
confidence: 99%
“…But while toxicity assays are available for many countries (e.g., Argentina [365, 633], Bahrain [634], Bangladesh [635], Brazil [329, 418, 636, 637], Canada [638], Chile [639], China [640], Cuba [641, 642], Ecuador [643], Guatemala [644646], Honduras [647], India [648], Kenya [627, 649], Mexico [650], Nicaragua [651], Nigeria [652], Panama [653], Papua New Guinea [654], Philippines [655], Uruguay [656], and USA [657659], no data exists on the potential toxicity of Peruvian medicinal species.…”
Section: Two Decades Of Traditional Medicine Research In Northern mentioning
confidence: 99%